2020
DOI: 10.3390/ijerph17239115
|View full text |Cite
|
Sign up to set email alerts
|

Physical Fitness Level and Mood State Changes in Basic Military Training

Abstract: The purpose of this study was to investigate the change of fitness level and mood states in the basic military training (BMT) for midshipmen using latent growth model analysis. A total of 285 midshipmen were selected as participants in BMT. The results were as follow: First, the slope of low initial fitness level increase higher than high initial fitness level. Second, there is no significant on relation between the slope of total mood disturbance score (TMD) and initial TMD level. Third, initial fitness level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…The influence of MSDs on overall health varies on the severity of the condition, the kind of MSD, and the individual's overall health (Itismita Mohanty et al 2019). MSDs may cause physical inactivity due to discomfort, stiffness, and reduced mobility (Hyoyeon Ahn et al 2020). People suffering with MSDs may struggle to do physical activities such as exercising, athletics, or even everyday tasks such as moving, walking, or sitting for a long time (Rafael E. Reigal et al 2020).…”
Section: Personal Risk Factorsmentioning
confidence: 99%
“…The influence of MSDs on overall health varies on the severity of the condition, the kind of MSD, and the individual's overall health (Itismita Mohanty et al 2019). MSDs may cause physical inactivity due to discomfort, stiffness, and reduced mobility (Hyoyeon Ahn et al 2020). People suffering with MSDs may struggle to do physical activities such as exercising, athletics, or even everyday tasks such as moving, walking, or sitting for a long time (Rafael E. Reigal et al 2020).…”
Section: Personal Risk Factorsmentioning
confidence: 99%
“…Physical fitness should be considered a fundamental aspect in terminating a student's functional capacity, (Medrano-Ureña et al, 2020). Ahn et al, (2020) in their research revealed that fitness is very important for cadets to follow basic military training. Likewise, the members of the student regiment should also consider physical fitness.…”
Section: Introductionmentioning
confidence: 99%
“…La Escuela Militar de Cadetes en Colombia, al igual que la mayoría de las academias militares a nivel mundial, tiene como rol fundamental en la sociedad, la formación de los futuros oficiales del Ejército, cuya educación impartida se enfoca en las áreas del conocimiento militar como son el desarrollo y mantenimiento de un acondicionamiento físico adecuado, valores sobre ideología nacional, conceptos de seguridad y defensa nacional que son cualidades que los cadetes deben cultivar e interiorizar (-Escuela Militar de Cadetes José María Córdova, s. f.; Ahn et al, 2020). Para alcanzar el objetivo de crear una cultura de mejorar y mantener un acondicionamiento físico adecuado, en el cuarto año de estudios militares, se realiza el Curso Avanzado de Combate (CAC), en donde los cadetes permanecen inmersos durante ocho semanas en un escenario que simula y recrea un ambiente hostil cercano a las condiciones climáticas, locativas y de exposición a las que normalmente se ven sometidos en la vida real en el área de operaciones.…”
Section: Introductionunclassified